Participation and Learning Perspectives on Education and the Environment, Health and Sustainability - Reid, Alan.; Jensen, Bjarne Bruun; Nikel, Jutta; Simovska, Venka; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This ground-breaking collection brings together a diverse range of perspectives on the philosophy, design and experience of participatory approaches within education and the environment, health and sustainability. Chapters address participatory work with children, youth and adults in both formal and non-formal settings. Authors combine reflections on experience, models and case studies of participatory education with commentary on key debates and issues. The book will be a valuable resource for researchers and advanced students with interests in learning, research and key concepts in environmental education, health education, and education for sustainable development, and professionals and practitioners engaged in planning and evaluation.
Participation and Learning: Developing Perspectives on Education and the Environment, Health and Sustainability -- Stepping Back from 'The Ladder': Refl ections on a Model of Participatory Work with Children -- Differentiating and Evaluating Conceptions and Examples of Participation in Environment-Related Learning -- Learning in and as Participation: A Case Study from Health-Promoting Schools -- Environmental Learning and Categories of Interest: Exploring Modes of Participation and Learning in a Conservation NGO -- Participation and the Ecology of Environmental Awareness and Action -- Participation, Situated Culture, and Practical Reason -- From Practice to Theory: Participation as Learning in the Context of Sustainable Development Projects -- Participation and Sustainable Development: The Role and Challenges of Mediating Agents -- Mental Ownership and Participation for Innovation in Environmental Education and Education for Sustainable Development -- Participation, Education, and Democracy: Implications for Environmental Education, Health Education, and Education for Sustainable Development -- What Comes Before Participation? Searching for Meaning in Teachers' Constructions of Participatory Learning in Environmental Education -- Participatory Pedagogy in Environmental Education: Reproduction or Disruption? -- Elusive Participation: Methodological Challenges in Researching Teaching and Participatory Learning in Environmental Education -- Student Participation in School Ground Greening Initiatives in Canada: Refl ections on Research Design Decisions and Key Findings -- Researching Participation using Critical Discourse Analysis -- Youth Participation in Local Environmental Action: An Avenue for Science and Civic Learning? -- A Clash of Worlds: Children Talking About their Community Experience in Relation to the School Curriculum -- Sustainability Education, Whole School Approaches, and Communities of Action -- School Councils as an Arena for Pupils' Participation in Collaborative Environmental Education Projects.
Keywords: ENVIRONMENTAL SCIENCES; CURRICULUM PLANNING; SCIENCE -- STUDY AND TEACHING; ENVIRONMENTAL MEDICINE; ENVIRONMENT; ENVIRONMENT, GENERAL; SOCIOLOGY OF EDUCATION; CURRICULUM STUDIES; SCIENCE EDUCATION; ENVIRONMENTAL HEALTH